Antimicrobial activities of endophytic fungi metabolites / Nor Izzati Mat Daud - Mat Daud, Nor Izzati (2012)
The rising of resistances toward present antibiotics have long been reported by many physicians, and researchers have become concern by this issue. In order to keep searching novel drugs that will be available in the future, this project research aims to contribute in collecting data from the endophytic fungi obtained from Malaysian environment (Puncak Alam forest) as part of a large drug discovery programme. The study was done to investigate the secondary metabolites produced by endophytic fungi TH2S14 and TH3R30 that can be used for medicinal plant purpose. The endophytic fungi were cultured on Potato Dextrose Agar Plate (PDA), and extracted using ethyl acetate as a solvent. Then, the fungal extracts had been subjected to analytical High performance liquid chromatography (HPLC) using a diode array detector (DAD) and proceed to Semi-preparative HPLC to collect the extract fractions. The antimicrobial activity was tested only to the fractions of fungus TH2S14 because of time constraint. From the antibacterial activity test by MTT assay, the extract fractions only showed positive result against Enterococcus faecium and Escherichia coli not to Staphylococcus aureus and Pseudomonas aeruginosa as stated in the reference. This may be due to the poor techniques of antibacterial activity test being conducted.